Analysis of the Profit Allocation and Distribution Policy of a Group of Algerian Economic Institutions During the period (2017-2022) - Hadjadj , Mustapha; Bouchekifa , Hamid (Finance and Business Economies Review, 2023)
The study examines the impact analysis of a specific set of factors that determine dividend distribution policy within a sample of 06 Algerian economic institutions from 2017 to 2022. This investigation employs panel data analysis, utilizing six financial variables including the ratio of distributed profits per share as the dependent variable. Additionally, factors such as profitability, liquidity, growth, financial leverage, and risk size serve as explanatory variables. The findings reveal a statistically significant relationship between profitability, liquidity, and financial leverage with the ratio of distributed profits. However, other explanatory variables, namely growth and risk size, fail to exhibit statistical significance in explaining variations in the dependent variable within the institutions sampled in the study.